Case study of software product line construction in e-insuBanking and customisation mechanism. (1st January 2014) - Kim, Jeong Ah; Kim, SunTae
Cyber customer support domain is increasingly spread in life insurance industry so that the necessity of product line is requested. Because many channel systems in insurance domain are required for specific customer segmentation. Each channel system should be based on main business information system but each has little differences in user interface and service features. For improving the productivity in this domain, software product line engineering can be adopted. In this paper, we suggested software product line architecture and customising mechanism in e-insuBanking domain. With suggested architecture and customisation environment, it is possible to configure the new software product from the product line.